2013
DOI: 10.1016/j.urology.2013.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Genital Injury: An Analysis of the National Electronic Injury Surveillance System

Abstract: Objective To describe the characteristics of pediatric genital injuries presenting to United States emergency departments (EDs). Methods A retrospective cohort study utilizing the U.S. Consumer Product Safety Commission (CPSC) National Electronic Injury Surveillance System (NEISS) from 1991-2010 to evaluate pediatric genital injuries was performed. Results Pediatric genital injuries represented 0.6% of all pediatric injuries with the incidence of injuries rising through the period studied, 1991-2010. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 19 publications
3
28
0
1
Order By: Relevance
“…This may account for the higher proportion of AG injuries (0.23%) in children attending the ED. Our finding that very few injuries required hospital admission concurs broadly with those previously reported (Scheidler et al, ; Casey et al ., ; Tasian et al , ). Admission is usually to ensure that the cause of bleeding is adequately explored (both by history, and if there is any evidence of a penetrative element, to ensure that no internal organs are damaged, with an examination under anaesthesia), but in our cohort, admission to manage pain causing retention of urine was also common.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This may account for the higher proportion of AG injuries (0.23%) in children attending the ED. Our finding that very few injuries required hospital admission concurs broadly with those previously reported (Scheidler et al, ; Casey et al ., ; Tasian et al , ). Admission is usually to ensure that the cause of bleeding is adequately explored (both by history, and if there is any evidence of a penetrative element, to ensure that no internal organs are damaged, with an examination under anaesthesia), but in our cohort, admission to manage pain causing retention of urine was also common.…”
Section: Discussionmentioning
confidence: 97%
“…The sparse epidemiological data comparing accidental and abusive AG injuries are often related to referral populations where the injuries may be at the severe end of a spectrum. Casey et al () reported a ten‐year national survey of children presenting to a ‘representative group’ of EDs in the USA. Paediatric genital injuries represented 0.6 per cent of all paediatric injuries and 95 per cent were treated and discharged without hospital admission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preputial injuries are seen in association with other injuries. According to the National Electronic Injury Surveillance System (NEISS), genital injuries represented 0.6% of all pediatric injuries [5].…”
Section: Discussionmentioning
confidence: 99%
“…straddle injuries, motor vehicle accidents, etc.) or due to abuse and as a result can lead to long-term physical and/or psychological sequelae for the victims [5,6].…”
Section: Introductionmentioning
confidence: 99%